Healthcare Worker Mental Health and Wellbeing During COVID-19: Mid-Pandemic Survey Results - Young, Kevin P.; Kolcz, Diana L.; Ferrand, Jennifer; O’Sullivan, David M.; Robinson, Kenneth (Frontiers in Psychology, 2022)
Introduction/Background HealthCare worker (HCW) mental health and wellbeing are uniquely affected by the complexities of COVID-19 due to exposure to the virus, isolation from family and friends, risk and uncertainty. Little if any inquiry has examined the effects on an entire healthcare system, particularly immediately post-surge. We sought to examine the prevalence of psychiatric symptoms and behavioral health difficulties as a healthcare system transitioned out of the first wave. We assessed the effects of work role, setting and individual diversity factors on employee distress and coping strategies. Materials and Methods This was an Institutional Review Board approved, unfunded, voluntary survey sent via REDCap link, to all employees of Hartford HealthCare, a mid-sized healthcare system (N ≈ 29,900) between May 15th and June 26th, 2020. Two system-wide emails and two emails targeting managers were sent during this time frame. Eight thousand four hundred and ninety four employees (28.4% of all e-mails distributed) participated in the survey, representing clinical, support, administrative, and medical staff across hospital, outpatient, residential, and business settings. The survey contained items assessing personal background, work environment/culture, and formal measures, including: patient health questionnaire-9 (PHQ-9), general anxiety disorder-7 (GAD-7), primary care post-traumatic stress disorder screen for DSM-5 (PC-PTSD), alcohol use disorders identification test (AUDIT-C), and the insomnia severity index (ISI). Results Almost 1/3 of respondents (31%) reported symptoms of clinically significant anxiety; 83% moderate to severe depression; and 51% moderate to severe insomnia. Thirteen percent screened positive for post-traumatic stress disorder. Frontline staff (p ≤ 0.001 vs. others) and females (p < 0.001 vs. males) endorsed the highest levels of distress, while race (p ≤ 0.005) and ethnicity (p < 0.03 for anxiety, PTSD and insomnia) had a complex and nuanced interaction with symptoms. Conclusion Pandemic stress effects all healthcare employees, though not equally. The effects of work role and environment are intuitive though critical. These data suggest individual diversity factors also play an important role in mental health and wellbeing. All must be considered to optimize employee functioning.